1999
DOI: 10.1212/wnl.53.8.1698
|View full text |Cite
|
Sign up to set email alerts
|

Use of the brain parenchymal fraction to measure whole brain atrophy in relapsing-remitting MS

Abstract: Article abstract-Background: Episodic inflammation in the CNS during the early stages of MS results in progressive disability years later, presumably due to myelin and axonal injury. MRI demonstrates ongoing disease activity during the early disease stage, even in some patients who are stable clinically. The optimal MRI measure for the destructive pathologic process is uncertain, however. Methods: In this post-hoc study, MRI scans were analyzed from patients with relapsing MS participating in a placebo-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
251
3
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 660 publications
(277 citation statements)
references
References 22 publications
15
251
3
4
Order By: Relevance
“…The concept that a threshold for brain pathology needs to be met before cognitive decline becomes clinically apparent (Figure 2) means that irreversible axonal damage and brain tissue loss under a certain threshold may accumulate in relatively asymptomatic patients. Once the cognitive brain capacity has been surpassed and functional compensatory mechanisms fail, cognitive disability may become clinically apparent 34, 35, 36. This could explain why patients with some but minor brain atrophy or with a small lesion burden often show only limited cognitive deterioration relative to brain pathology 37.…”
Section: Discussionmentioning
confidence: 99%
“…The concept that a threshold for brain pathology needs to be met before cognitive decline becomes clinically apparent (Figure 2) means that irreversible axonal damage and brain tissue loss under a certain threshold may accumulate in relatively asymptomatic patients. Once the cognitive brain capacity has been surpassed and functional compensatory mechanisms fail, cognitive disability may become clinically apparent 34, 35, 36. This could explain why patients with some but minor brain atrophy or with a small lesion burden often show only limited cognitive deterioration relative to brain pathology 37.…”
Section: Discussionmentioning
confidence: 99%
“…76 In the pivotal trial of IFN␤1a-IM, whole-brain atrophy was measured using the brain parenchymal fraction method in 68 patients randomized to interferon-␤1a and 72 patients randomized to placebo. 77 There was a 55% reduction in brain atrophy (Ϫ0.233% in IFN, compared with Ϫ0.521% in placebo) seen with interferon therapy in the second year of therapy, but no effect during the first year. Analysis of a subgroup that underwent frequent MRIs during the first year of a separate trial of IFN␤1a-IM showed that 68% of the first-year brain parenchymal fraction decrease occurred during the first 4 months of treatment.…”
Section: Effect On Brain Atrophymentioning
confidence: 95%
“…However, neuroimaging studies revealed microglia activation with minimal inflammatory cell infiltrates in proximity of cortical axonal transections [19]; this gray matter abnormality occurs surprisingly early and correlates much better with permanent disability, demonstrating that microglia activation in gray matter correlates with neuron loss and MS onset ( [37,51,201,230]). …”
Section: The Eae Animal Modelmentioning
confidence: 99%